Brighton v RSPCA NSW: Appeals and Lessons Four Years On - Kathryn Jurd; Sophie Riley (Animals)
Animal law has the potential to initiate improvements for animal wellbeing. However, this largely depends on how effectively the law bridges the legal chasm between animal welfare and animal suffering, a chasm the authors refer to as the welfare gap. When the law does not adequately address this gap, where regulation subordinates animal interests to human interests, it results in weak animal protection that does little more than regulate to a standard that avoids a life not worth living. The authors analyse a series of cases involving the RSPCA and Brighton, in which Brighton was charged with serious animal cruelty pursuant to s 530 of the Crimes Act 1900 (NSW). He stabbed a dog with a pitchfork; after failing to kill the dog, he suspended it from a tree branch by a leash attached to its collar and struck the dog several times on the head with a mallet, finally killing him. Brighton was found guilty in the NSW Local Court and appealed to the NSW Supreme Court, where Rothman J allowed the appeal, holding that Brighton had exterminated a pest animal. This led to protracted litigation, including to the NSW Court of Appeal, a second hearing in the Local Court and a further appeal to the Supreme Court. In August 2020, Sophie Riley published a case note and commentary on the litigation up to the Rothman J appeal. This paper evaluates the litigation that followed, identifying how regulatory failures have entrenched the welfare gap. Regulatory failures include inadequate and aged legislative protections for a confined subset of animals. In NSW, animal sentience is not enshrined in legislation; the law limits the types of animals protected by anti-cruelty law; fundamental statutory language remains undefined, for example terms such as “pest animal” and “exterminate”; and challenges abound for adducing sufficient evidence to prove subjective criminal intent. These deficiencies pose significant challenges for practitioners and judicial officers, particularly when complex statutory interpretation is required in the busy and fast-paced summary jurisdiction. This paper concludes that legislators should consider modernising the law, removing ambiguity, and settling minimum standards for a good life for animals, taking into account the welfare aspects described in Mellor’s Five Domains model.